2017
DOI: 10.1107/s1600576717003235
|View full text |Cite
|
Sign up to set email alerts
|

The real background and peak asymmetry in diffraction on nanocrystalline metals

Abstract: A method to analytically calculate the column length distribution (CLD) from a single reflection of a strain‐free nanocrystalline metal is proposed. It involves precise estimation of the peak background level using a physical criterion – the positivity of the CLD. The method can be applied to materials showing a dependence of the lattice constant on the crystal size, because of which the diffraction peaks display asymmetry. The analysis can provide an estimation of this dependence. Results for platinum and gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…We would like to point out that there are also studies that do not find significant evidence of stress, for example, in gold and platinum particles. 70 However, in these cases, the peak profiles were found to be of asymmetric shape. Cline et al reported on the development of a zinc oxide standard reference material for the determination of domain sizes.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We would like to point out that there are also studies that do not find significant evidence of stress, for example, in gold and platinum particles. 70 However, in these cases, the peak profiles were found to be of asymmetric shape. Cline et al reported on the development of a zinc oxide standard reference material for the determination of domain sizes.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Further studies are needed to provide more precise ϵ, σ, u , and D hkl data, which in particular also provide uncertainties. We would like to point out that there are also studies that do not find significant evidence of stress, for example, in gold and platinum particles . However, in these cases, the peak profiles were found to be of asymmetric shape.…”
Section: Nanocrystalsmentioning
confidence: 84%
“…The background subtraction required careful consideration of (a) the contributions of the specimen holder (sintered glass plate),(b) sample amorphous component and, (c) the scattering from the adsorption layer on the sample surface as well as from the content of the pores in the sample. The background subtraction could be performed precisely starting from estimation of the background profile for the sample in He (the He1 experiment stage is considered) by fitting its polycrystalline peaks to pairs (reflecting Cu K α 1 and K α 2 lines) of Voigt profiles following rules described before 37 . The residual scattering profile resulting from the best fit was accepted as a background for He.…”
Section: Diffraction Pattern Analysismentioning
confidence: 99%
“…[5][6][7][8][9][10], to precisely control the hydrogenation pathway and, thus, to obtain desired products. The main scope of this work is to describe surface adsorption phenomena by in situ infrared (IR) spectroscopy that can later be utilised for studies of catalyst surface structure changes by means of various structuresensitive techniques arranged as in operando setups, including in operando electron microscopy, 11 in operando powder X-ray diffraction 12,13 and others e.g. ref.…”
Section: Introductionmentioning
confidence: 99%